2013
DOI: 10.1504/ijtel.2013.059087
|View full text |Cite
|
Sign up to set email alerts
|

Improving academic outcomes: does participating in online discussion forums payoff?

Abstract: This paper reports on a study investigating the potential relationship between a student's discussion forum activity and their academic performance. The study also examined the influence of the delivery method (i.e. blended or fully online) on the impact that forum participation may have on a student's final mark. To address these aims, student forum participation data and teaching delivery method were extracted from the universities Learning Management System (LMS). The analysis identified that students who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
8
0
4
Order By: Relevance
“…The findings are consistent with our earlier work (Carceller et al, 2013) that an academic advantage may be derived for those students that actively participate in their online discussion forum. This aligns with the idea that communication activity represents investment in social networks and in the social capital cycle.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings are consistent with our earlier work (Carceller et al, 2013) that an academic advantage may be derived for those students that actively participate in their online discussion forum. This aligns with the idea that communication activity represents investment in social networks and in the social capital cycle.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, discussion forum activity can facilitate student-centred learning (Ellis, 2001), and support student engagement (Jahnke, 2010); sense of community (Davies & Graff, 2005;Dawson, 2006;Rovai, 2002) and academic performance (Carceller, Dawson, & Lockyer, 2013;Morris, Finnegan, & Wu, 2005). While the pedagogical benefits associated with discussion forum participation have now been well established, there has, however, been limited investigation into the types of relationships that manifest in this medium and how these relationships can be leveraged for academic advantage regardless of the delivery mode (i.e., blended or fully online).…”
Section: Introductionmentioning
confidence: 99%
“…First, we did not assess learning outcomes for the presentations as this was beyond the scope of this exploratory study. Some previous studies demonstrated that online discussion forums increased student performance (3,4,7), whereas other studies showed no correlations between student performance and online discussion (24). In our study, many students did report in the survey that learning was enhanced with VoiceThread.…”
Section: In-class Voicethread Bothmentioning
confidence: 94%
“…Among the remaining papers, we distinguished a set (11 papers), mainly proposing models, indicators, visualizations or analytic methods, which applied their proposed model/analysis to a dataset gathered from authentic educational contexts (e.g., the log files generated during a course). The scale of these authentic dataset analyses varied greatly: certain studies analysed data representing a few dozen students, while others used massive multi-course ensembles (the extreme case being Carceller et al (2013), in which n students = 12901). The median size of these datasets, however, was n students = 252.…”
Section: Action-related (34)mentioning
confidence: 99%